New Insular Record of the Giant Water Bug, Lethocerus patruelis (Hemiptera: Belostomatidae), from the Northeastern Aegean - Giorgos Stavrianakis; Asimina Koukoura; Apostolos Christopoulos; Yiannis G. Zevgolis (Diversity, 2025)
Lethocerus patruelis (Stål, 1854) is a large aquatic hemipteran and the only European representative of the family Belostomatidae. Commonly known as the giant water bug, this species was historically restricted to the Balkans, Anatolia, and parts of the Middle East, but has exhibited a marked westward and northward range expansion in recent decades. In this study, we report the first confirmed occurrence of L. patruelis on Lesvos Island, in the northeastern Aegean Sea, based on a direct observation made within a wastewater treatment facility. The individual was identified in situ using diagnostic morphological traits and photographed without disturbance. This finding extends the known insular distribution of the species and underscores its capacity to exploit anthropogenically modified aquatic systems. Given the island’s rich mosaic of natural and artificial wetland habitats—including over 200 mapped sites—Lesvos may offer suitable conditions for the establishment of local populations. This record highlights the need for targeted surveys and long-term monitoring across under-sampled insular landscapes.